Perbandingan Pendapatan Petani Padi Sawah Berdasarkan Status Penguasaan Lahan (Studi Kasus di Lingkungan Betang Kelurahan Baju Bodoakecamatan Maros Baru Kabupaten Maros) - Hasniah Hasniah; Mohammad Anwar Sadat; Andi Nur Imran (Jurnal Agribis, 2021)
This recearchwas conducted in teh Betang neighborhood, Baju Bodoa Village, Maros Baru District, Maros Regency. This location was chosen with the consideration that tthe respondent has been managing lowland rice farming for a long time. There are two data used, namely: primary data is data that directly provides information to data collectors by asking questions according to the contest of the questionnare and secondary data, namely data obtained from other parties or in the form of documents from certain agencies. The purpose of this study was to compare the income of rice farmers based on land ownership status in the Betang neighborhood, Baju Bodoa Village, Maros Baru District, Maros Regency. The data that has been collected is then calculated to get the data needed in the analysis. This study uses quantitative data to determine the income of lowland rice farmers based on land ownership status in the Betang Environment, Baju Bodoa Village, Maros Baru District, Maros Regency. From the results of the study, it can be seen that the income of the owner farmer is greater than that of the non-owner farmer